New variety: SCRID 091-38-4-3-4-1-1-5 (F188) for Madagascar - CGIAR Research Program on Rice (2020)
The variety was evaluated in the DHS (Distinctiveness, Homogeneity and Stability trials) and approved by the institution responsible for the variety registration process. It is thus registered in the variety catalog